Development and Validation of a Simple UV-Vis Spectrophotometric Method for the Quantitative Determination of Amoxicillin in Pharmaceutical Dosage Forms - Ben Hander, Gazala; Mousa, Hawa; Alajtal, Adel (AlQalam Journal of Medical and Applied Sciences, 2025)
A simple, sensitive, and inexpensive UV/visible spectrophotometric approach was developed and validated for the quantitative measurement of amoxicillin (AMX) in pharmaceutical dosage forms. The approach demonstrated excellent linearity (r² = 0.9994) across the concentration range of 1.0-15.0 µg mL⁻¹ by measuring absorbance at 228 nm. The determined limits of detection and quantification were established at 0.56 and 1.72 µg mL-1 for AMX, respectively. Values of relative standard deviation (RSD) below 2% indicated remarkable repeatability and consistency; intra-day and inter-day studies confirmed accuracy. Recovery tests conducted at three concentration levels yielded results within the acceptable range of 94.15% to 108%, demonstrating the accuracy of the method. The validated method was successfully used to analyze various commercial amoxicillin products in tablet and capsule forms because all the tested samples met the required quality standards. These findings demonstrate that the proposed spectrophotometric method is consistent and adequate for routine quality monitoring of amoxicillin in pharmaceutical formulations.